2020
DOI: 10.1161/circresaha.119.316388
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of LAPTM4B Contributes to the Impairment of the Autophagic Flux via Unopposed Activation of mTORC1 Signaling During Myocardial Ischemia/Reperfusion Injury

Abstract: Rationale: Impaired autophagic flux contributes to ischemia/reperfusion (I/R)-induced cardiomyocyte death, but the underlying molecular mechanisms remain largely unexplored. Objective: To determine the role of lysosomal-associated transmembrane protein 4B (LAPTM4B) in the regulation of autophagic flux and myocardial I/R injury. Methods and Results: LAPTM4B was expressed in murine hearts but downregulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 33 publications
5
58
0
Order By: Relevance
“…The myocardial I/R model was induced as previously described 30 . Briefly, male C57BL/6 mice at 10‐12 weeks‐old were anesthetized via intraperitoneal injection (i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The myocardial I/R model was induced as previously described 30 . Briefly, male C57BL/6 mice at 10‐12 weeks‐old were anesthetized via intraperitoneal injection (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant adenoviruses (Ad) expressing short hairpin RNA were prepared as reported previously 30,33,34 . Detailed experimental methods are available in the Supplemental Materials section.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The membrane expands and bends, and then a spherical autophagosome is generated. Using electron microscopic examination of the obverse, it has been found that the diameter of autophagosomes ranges from 0.5 to 1.5 μm in mammals and ∼0.4 to 0.9 μm in yeast ( Takeshige et al, 1992 ; Gu et al, 2020 ). Besides autophagosomes, autophagy precursors (which include the cytoplasm, organelles, or bacteria) and autophagolysosomes (autophagosomes that bind to the lysosome) are also vital subcellular structures.…”
Section: Determining Cell Morphology Of Rcdsmentioning
confidence: 99%